KONSTRUKSI NILAI SOSIAL RELIGIUS DALAM PEMBENTUKAN KARAKTER SISWA UNTUK MENINGKATKAN KUALITAS INTERAKSI SOSIAL DI LINGKUNGAN SEKOLAH - Suparman Suparman; Putriyani S (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2026)
This study was motivated by declining student social interaction quality in the modern era, characterized by low empathy, reduced social awareness, and increasing individualistic behavior. It aims to analyze the construction of socio-religious values in shaping student character and improving social interactions at MA Muhammadiyah Enrekang. A descriptive qualitative approach was employed, with the researcher as the primary instrument supported by interviews, observations, and documentation. Data were collected from primary and secondary sources through in-depth interviews, participant observation, and document analysis. Data analysis followed the Miles and Huberman interactive model, including data reduction, presentation, and conclusion drawing, while validity was ensured through source, technique, and time triangulation. The findings reveal that socio-religious values are implemented through classroom learning, habituation programs, and teacher role modeling. However, their internalization remains inconsistent among students. The study highlights the need for integrative and sustainable strategies to strengthen socio-religious values and enhance students’ social interaction quality.